Coronary artery calibre after direct intra-arterial infusion of epoprostenol (prostacyclin). Issue 5 (November 1988) - Wilson, J; Silverton, N P; Baig, M W; Perrins, E J; Smith, D R; Davies, J A; Prentice, C R
Abstract : Because epoprostenol (prostacyclin) is a prostaglandin that causes vasodilatation and inhibits platelet function it may be of benefit during coronary artery angioplasty. The safety and capacity of intracoronary epoprostenol to dilate coronary arteries were assessed in 16 patients undergoing routine coronary angiography. The view that best displayed the left epicardial coronary arteries was selected as a control for each patient. Intracoronary epoprostenol was then given and the angiogram was repeated in the chosen view. The procedure was repeated twice: once with a higher dose of epoprostenol and once after intracoronary isosorbide dinitrate. Angiograms were coded and analysed by an observer who was unaware of the treatment. The calibre of the arteries was measured from traced projections of the angiograms. The blood pressure, heart rate, and electrocardiogram were recorded throughout. The first two patients were given epoprostenol infusions of 2.5 and 5.0 ng/kg per minute to assess safety, and there were no untoward reactions. The next ten patients had epoprostenol infusions of 5.0 and 7.5 ng/kg per minute followed by intracoronary isosorbide dinitrate. No haemodynamic disturbances occurred and coronary luminal calibre did not change with epoprostenol (mean (SD) luminal diameter: 2.85 (0.62) mm control, 2.80 (0.61) mm at 5.0 ng/kg, and 2.80 (0.54) mm at 7.5 ng/kg), but it did increase significantly with isosorbide dinitrate (to 3.17 (0.36) mm). The last four patients had epoprostenol infusions of 7.5 and 10 ng/kg followed by intracoronary isosorbide dinitrate and two of them became hypotensive (one after epoprostenol and one after isosorbide dinitrate). Coronary luminal calibre did not change significantly (3.5 (0.45) mm control, 2.96 (0.81) mm at 7.5 ng/kg, 3.45 (0.96) mm at 10 ng/kg, and 3.20 (0.61) mm with isosorbide dinitrate). Eight patients developed tall T waves on the electrocardiogram during epoprostenol infusion but none had arrhythmias. The results indicate that clinically tolerable doses of intracoronary epoprostenol do not significantly dilate the epicardial coronary arteries. This route of administration is therefore unlikely to be of use during coronary angioplasty, although the antiplatelet action of intravenous epoprostenol might help to prevent restenosis.